Kearifan Lokal Bangunan dan Tradisi Hari Raya Rumah Godang - Zulfan Saam; Dhina Yuliana; Sarjan Sarjan (Pelantar Press, 2025)
The development of science and technology as well as the increasing need for space have an unfavorable impact on the heritage of historic buildings. There are times when the building is not maintained.The godang house or traditional house in Kuantan Singingi is a heritage building that is tens or even hundreds of years old. Many historical values and educational values contained in the Godang house building. The purpose of this study is to analyze the local wisdom value of the godang house building in supporting the concept of sustainable buildings and the local wisdom value contained in the tradition of praying at the godang house. This type of research is survey research. The Research data collection techniques are observation, and deep interviews. The results of the study showed that the godang house building is an environmentally friendly building. The local wisdom values of the Rumah Godang holiday are: the value of togetherness, preventing tribal conflicts, cultural continuity and cultural laboratories. The educational values contained in the Godang house building are to foster the value of togetherness, to prevent inter-tribal marriages, cultural laboratories, environmental behavior and strengthen kinship